Intravenous delivery of adeno-associated virus 9-encoded IGF-1Ea propeptide improves post-infarct cardiac remodelling - Gallego,Colon EJ; Villalba,M; Tonkin,J; Cruz,F; Bernal,JA; Jimenez-Borreguero,L; Schneider,M; Lara,E; Rosenthal,N (npj Regenerative Medicine, 2016)
The insulin-like growth factor Ea propeptide (IGF-1Ea) is a powerful enhancer of cardiac muscle growth and regeneration, also blocking age-related atrophy and beneficial in multiple skeletal muscle diseases. The therapeutic potential of IGF-1Ea compared with mature IGF-1 derives from its local action in the area of synthesis. We have developed an adeno-associated virus (AAV) vector for IGF-1Ea delivery to the heart to treat mice after myocardial infarction and examine the reparative effects of local IGF-1Ea production on left ventricular remodelling. A cardiotropic AAV9 vector carrying a cardiomyocyte-specific IGF-1Ea-luciferase bi-cistronic gene expression cassette (AAV9.IGF-1Ea) was administered intravenously to infarcted mice, 5 h after ischemia followed by reperfusion (I/R), as a model of myocardial infarction. Virally encoded IGF-1Ea in the heart improved global left ventricular function and remodelling, as measured by wall motion and thickness, 28 days after delivery, with higher viral titers yielding better improvement. The present study demonstrates that single intravenous AAV9-mediated IGF-1Ea Gene Therapy represents a tissue-targeted therapeutic approach to prevent the adverse remodelling after myocardial infarct.